Localize surface plasmon resonance of silver nanoparticles using Mie theory - Alzoubi, F. Y.; Ahmad, Ahmad A.; Aljarrah, Ihsan A.; Migdadi, A. B.; Al-Bataineh, Qais M. (Journal of materials science. Materials in electronics, 2023)
In this work, the optical properties of silver nanoparticles (AgNPs) were explored using Mie theory compared with the experimental AgNPs using the chemical reduction method. Mie’s theory is suited for accurately evaluating the scattering, absorption, and extinction cross-sections of spherical AgNPs. Therefore, the wavelength of localized surface plasmon resonance (LSPR) in the optical spectra of the spherical AgNPs was calculated. The experimental AgNPs have a spherical shape with an average particle size of 30 nm. In addition, the crystalline structure of AgNPs was found to be cubic with fcc structure with lattice constant a = 4.155 Å. Moreover, the excitation of the LSPR of the AgNPs was simulated using the finite-difference time-domain (FDTD) method at different wavelengths to explore the LSPR phenomena. The results show that spherical AgNPs are the most widely used materials in biosensors, biomedicine, optoelectronic devices, and solar cells due to their surface plasmon resonances in the visible spectrum region.